Exploring the Role of Menu Design in Attracting Customers: A Case Study of Kitchen ASIA - Romadhon, Fahmi; Adhitama, Putu Ion Agus Pribadi; Suprianto, Donny Ardin (Akademi Komunitas MAPINDO, 2024)
Visual design menu is one of important thing in attracting interest customer. This Study aims to explore structure and components of visual design menu in attracting interest customer in Kitchen ASIA. The research use qualitative approach with descriptive analysis. It examines the structural components of the menu, including layout, typography, color use, F and B picture, and price to describe and analyze how they affect interest and purchasing decision for customers. The findings show that the menu is simple designed, bilingual descriptions, and provide informative and clear description of the menu. They influence the customer in making interest and giving positive experience. However, there two things: the crossed-out prices and the absence of a dedicated dessert section, could be improved to enhance professionalism and customer satisfication. In conclusion, this study highlights the critical role that the visual menu design plays influencing customers’ interest and preference.